Gender-Specific Risk of Central Compartment Lymph Node Metastasis in Papillary Thyroid Carcinoma. (11th March 2018) - Sun, Yushi; Lv, Hongjun; Zhang, Shaoqiang; Bai, Yanxia; Shi, Bingyin
Abstract : Our aim was to evaluate the impact of gender on the predictive factors of central compartment lymph node metastasis (CLNM) in papillary thyroid carcinoma (PTC). A retrospective study of 590 patients treated for PTC was performed. Univariate and multivariate analyses showed that gender (female;P = 0.001 ), age (≥45 y;P < 0.001 ), tumor size (>1 cm;P < 0.001 ), and multifocality (P = 0.004 ) were independent predictive factors of CLNM in PTC patients. Patients were divided into male group (n = 152 ) and female group (n = 438 ). Age (≥45 y;P = 0.001 ), T4 (P = 0.006 ) and multifocality (P = 0.024 ) were independent predictive risk factors of CLNM in male patients. As for female patients, age (≥45 y;P < 0.001 ), tumor size (>1 cm;P < 0.001 ), multifocality (P = 0.002 ), and microcalcification (P = 0.027 ) were independently correlated with CLNM. The sensitivity of the multivariate model for predicting CLNM in male patients was 64.9%, specificity was 82.9%, and area under the ROC curve (AUC) was 0.764. As for female patients, the sensitivity was 55.7%, specificity was 77.9%, and AUC was 0.73. This study showed that the predictive factors of CLNM indeed varied according to gender. To have a more accurate evaluation of CLNM, different predictive systems should be used for male and female patients.